2011
DOI: 10.1002/gps.2508
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic criteria for apathy in clinical practice

Abstract: This study is the first one to test the diagnostic criteria for apathy in clinical practice. Results make the diagnostic criteria useful for clinical practice and research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
125
2
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(139 citation statements)
references
References 35 publications
6
125
2
6
Order By: Relevance
“…However, previous research has shown some evidence that apathy is multidimensional e.g.. [1,12], with the proposed diagnostic criteria of apathy recognizing the syndromatic nature of apathy [13,14] but without a thorough measurement of specific subtypes [15]. This has been observed in dementia using traditional one-dimensional assessment tools such as the Neuropsychiatric Inventory (NPI) [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, previous research has shown some evidence that apathy is multidimensional e.g.. [1,12], with the proposed diagnostic criteria of apathy recognizing the syndromatic nature of apathy [13,14] but without a thorough measurement of specific subtypes [15]. This has been observed in dementia using traditional one-dimensional assessment tools such as the Neuropsychiatric Inventory (NPI) [16].…”
Section: Introductionmentioning
confidence: 99%
“…Benoit et al (2011) suggested that imagining and anticipating an episode of pleasure (e.g., the receipt of a reward) with high emotional intensity and many phenomenological details might constitute an intrinsic source of motivation. It could be then hypothesized that the inability to project oneself into the future, and especially into future episodes of pleasure, may contribute to the existence of apathetic manifestations (e.g., loss of initiative or interest; see Mulin et al, 2011 for the diagnostic criteria of apathy) in schizophrenia. In this regard, it is interesting to consider the concept of anhedonia (characterized by a loss of pleasure) in parallel to apathy.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several studies on anhedonia in schizophrenia showed that patients have anticipatory pleasure deficits but normal levels of positive feelings (i.e., consummatory pleasure) when processing emotional stimuli (see Cohen and Minor, 2010, for a review). This may suggest that patients do not manifest disinterest (a dimension of apathy; see Mulin et al, 2011) in current activities. According to Heerey et al (2011), anticipatory pleasure deficits in schizophrenia patients could be due to degraded representations of future pleasurable events (e.g., rewards), which might account for their lower likelihood of pursuing pleasurable activities and thus their reduced GDB.…”
Section: Introductionmentioning
confidence: 99%
“…A significantly increased apathy score on the NPI has been reported for individuals in a clinical practice setting who fulfilled the proposed diagnostic criteria for apathy (20). …”
Section: Issues In Designing a Trial To Test Treatments For Apathymentioning
confidence: 99%